PRODUKSI METABOLIT SEKUNDER STEVIOSIDA PADA KULTUR KALUS STEVIA (Stevia rebaudiana Bert. M.) DENGAN PENAMBAHAN ZPT 2,4-D DAN PEG (Polyethylene Glykol) 6000 PADA MEDIA MS (Murashige & Skoog) - Laila, Fittriya Nur (El-Hayah : Jurnal Biologi, 2014)
Stevia rebaudiana is a member of the Asteraceae family, produce steviol glycosides (steviosida, rebaudiosida A, B, C, D, E and dulcosida A) which can be used as food additives such as food flavoring or sweetener in nutritional supplements. This study aims to determine the concentration of 2,4-D combination and PEG 6000 were effective in increasing the production of secondary metabolites in callus of stevia (Stevia rebaudiana Bert. M) in vitro. PEG 6000 is a way to manipulate media in vitro to increase secondary metabolite. This research used Completely Randomized Design (CRD) with 12 factorial combination with three replications. The first factor is the provision of plant growth regulator 2,4-D (1 mg / L, 2 mg / L, and 3 mg / L) and the second factor is the provision of PEG 6000 (0 mg / L, 5 mg / L, 15 mg / L, and 25 mg / L). The emerging callus (day), percentage (%) of explants callus (g), weight of callus, callus morphology (texture and color of the callus), and secondary metabolites steviosida were measured. Data were analyzed by analysis of variance (ANOVA) two way and to find a significant difference test Duncan's Multiple Range Test (DMRT) at 5% significance level. Steviosida secondary metabolites were measured using High Performance Liquid Cromatography (HPLC). The results showed that the combination treatment of 1 mg / L 2,4-D and 25 mg / L PEG 6000 is a combination of the most efficient way to get the amount of secondary metabolites steviosida 4.792 mg / g. Observations callus morphology (texture and color of the callus) showed that the compact callus textured and colored brown due to osmotic stress of PEG 6000 has a high content of secondary metabolites steviosida